Inside Agency: The Rise and Fall of Nortel - Fogarty, Timothy (Journal of business ethics, 2009)
By employing the theoretical template provided by agency theory, this article contributes a detailed clinical analysis of a large multinational Canada-headquartered telecommunications company, Nortel. Our analysis reveals a twenty-first century norm of usual suspects: a CEO whose compensation is well above those of his peers, a dysfunctional board of directors, acts of income smoothing to preserve the confidence of volatile investors, and revelations of financial irregularities followed by a downfall. In many ways, the spectacular rise and – sudden – fall of Nortel illustrates excesses of actors within, and contradictions of the system of corporate governance implied by the agency model. Furthermore, this case illustrates limitations of the agency framework in complex situations with short-term oriented investors.